Evaluation of the Primary Stability of 73 Implants with a New Macrogeometry in the Treatment of the Edentulous Maxilla by the All-on-Four Technique - Bruno Eduardo Sant'Anna Falce de Macedo; Rafael Manfro; Patrícia Tolentino da Rosa de Souza; Maurício Rosa; Gislaine Fernandes Felipe Garcia; Nayara Flores Macedo (Journal of Orofacial Sciences)
Introduction: Primary stability depends on factors such as bone quality and availability, surgical technique, implant microgeometry and is decisive to load implants immediately or wait for their osseointegration period. The implants used in this study (Implantes Maestro Implacil de Bortoli − São Paulo, SP, Brazil) have a conical shape with decompression chambers that increase the implant and bone contact area and reduce the implant insertion torque without affecting the primary stability. Evaluate the primary stability of 73 implants subjected to immediate loading and correlating this result with implant diameter and length. A cross-sectional clinical study. Methods and Material: Twenty one patients were selected clinically and by imaging with cone bean computed tomography. The implants were installed up to a torque of 35 N cm, measured at the end of the fixture installation. Statistical analysis used: Spearman’s correlation analysis and Mann–Whitney U test analysis, both with 5% significance. Results: The values obtained were 51.51 N cm for the 3.5 mm implants and 59.50 N cm for the 4.0 mm implants. These values were statistically significantly in favor of the 4.0 mm implants (P = 0.03). There was no statistically significant difference (P = 0.373) between the variation of the primary stability of the implants in relation to their length. Conclusions: Implants with larger diameter tend to have a greater primary stability, all of them showed average primary stability when sub-instrumented to perform immediate loading.